The Uplifting the Performance of Selected Learners Through the Use of Modular Approach and Online Teaching in the New Normal - Gerwin R. Lucero (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This study aimed to find out if there was an uplift in the performance of selected learners using modular approach and online teaching with intervention in the new normal. This study used the quantitative type of research and the descriptive-correlation method to collect the data pertinent to the issue of uplifting the performance of selected learners using a modular approach and online teaching in the new normal education system. The academic performance from the school record and a survey questionnaire as tools were used to gather the information needed for this study. Total enumeration of sampling technique, since they are a small group with a total of thirty (30) Grade 11 senior high school students from one section as participants in this study. The respondents of this study are the selected learners from Tañong High School in one section this school year 2021-2022 under the modular approach and online teaching in the new normal education system. The results revealed that the academic performance of the selected learners form Tañong High School was very good with an 85.2 weighted mean; the level effectiveness of the modular approach and online teaching is fairly effective, indicating that the modular approach and online teaching are to be uplifted the performance of learners; and there is a substantial or somehow effective connection between academic performance and effectiveness using the modular approach and online teaching as indicated by the Pearson Correlation.